The Interplay Between Coronavirus and Type I IFN Response - Xue, Wenxiang; Ding, Chan; Qian, Kun; Liao, Ying (Frontiers in Microbiology, 2022)
In the past few decades, newly evolved coronaviruses have posed a global threat to public health and animal breeding. To control and prevent the coronaviruses related diseases, understanding the interaction of coronavirus and host immune system is the top priority. Coronaviruses have evolved multiple mechanisms to escape or antagonize the host immune response to ensure their own replication. As the first line and main component of innate immune response, type I IFN response is able to restrict virus in initial infection stage, no wonder, IFN response is the prior target for virus to evade or antagonize. Gaining a profound understanding about the interaction between coronaviruses and type I IFN response will shed light on the development of vaccine and therapeutics. In this review, we provide an update on the current knowledge about strategies employed by coronaviruses to evade type I IFN response.